Lethal perinatal hypophosphatasia caused by a novel compound heterozygous mutation: a case report - Fengdan Yu; Junyi Wang; Xiaojing Xu (BMC Pediatrics, 2019)
Abstract Background Hypophosphatasia (HPP) is a rare hereditary disorder characterized by defective bone and tooth mineralization and deficiency of tissue non-specific alkaline phosphatase (TNAP) activity. The clinical presentation of HPP is highly variable, and the prognosis for the infantile form is poor. Case presentation This study reports a male infant diagnosed with lethal perinatal HPP. His gene analysis showed two heterozygous missense variants c.406C > T (p.R136C) and c.461C > T (p.A154V). The two mutations originated separately from his parents, consistent with autosomal recessive perinatal HPP, and the c.461C > T (p.A154V) was the novel mutation. Three-level structure model provide an explanation of the two mutated alleles correlating with the lethal phenotype of our patient. Results of SIFT, PolyPhen_2, and REVEL showed two mutations were pathogenic. Conclusions We demonstrated a case of perinatal lethal HPP caused by two heterozygous mutations, and one of which was novel. This finding will prove relevant for genetic counseling and perinatal gene testing for affected families.